Applicability of ARFI elastography in detecting elasticity changes of the equine superficial digital flexor tendon with induced injury - Bernardi, Nara Saraiva [UNESP]; da Cruz, Igor Cezar Kniphoff [UNESP]; Maronezi, Marjury Cristina [UNESP]; Santos, Maíra Moreira [UNESP]; Lera, Katiucha Rebeca Jennifer Lopes [UNESP]; Gasser, Beatriz [UNESP]; Aires, Luiz Paulo Nogueira [UNESP]; de Lacerda Neto, José Corrêa [UNESP]; Canola, Paulo Aléscio [UNESP]; Pozzobon, Ricardo; Uscategui, Ricardo Andrés Ramirez; Feliciano, Marcus Antônio Rossi (Wiley, 2022)
The objectives of this prospective, experimental study were to describe changes in the stiffness of the equine superficial digital flexor tendon (SDFT) after induced injury, deep digital flexor tendon (DDFT), accessory ligament (AL-DDFT), and suspensory ligament (SL) during 90 days of healing using acoustic radiation force impulse (ARFI) elastography. Eight healthy horses were selected. Preinjury B mode and ARFI evaluations were performed bilaterally in the palmar metacarpal region. Injury was induced only on the left forelimb (G2) by a single injection of collagenase in SDFT, 15 cm distal to the accessory carpal bone. The right forelimb was used as a control (G1). Evaluations were performed at eight timepoints: one before injury (T0) and seven (T1-T7) after injury (3, 15, 30, 40, 60, 75, and 90 days post-induction). Tendinopathies were visualized as hypoechoic areas with loss of parallel tendon fiber pattern. Injured SDFTs presented mainly cool colors (soft) from T1 to T3, and from T4, there was an increase in warm colors (hard), close to the appearance of tendons of G1. In the first four timepoints, there was a decrease in stiffness compared to G1 (P < 0.001). On T1 and T2, a cutoff value <6.21 m/s to determine tendinopathy of the SDFT was established (75.8% sensitivity and 92.03% specificity). Stiffness changes in the DDFT, AL-DDFT, and SL of injured limbs occurred at different timepoints. Tendinopathy significantly altered the stiffness of the injured tendon and the adjacent tissues. ARFI made it possible to detect these changes, helping to monitor the reparation of this injury.
Keywords: elastography; horse; ligament; musculoskeletal; stiffness; ultrasonography